Perceptions of Self-Care Among MSW Students: Implications for Social Work Education. (2nd October 2018) - Diebold, Josal; Kim, Wooksoo; Elze, Diane
ABSTRACT: For students new to social work, self-care is a strategy for addressing potentially negative impacts of the profession. Curiously, however, participation in a university's self-care program has been chronically low. The purpose of this study is to explore social work students' perceptions of self-care and to create a database for supporting changes in social work education. Qualitative data were collected via an online survey from MSW students. The findings revealed 5 categories for student perceptions of self-care, including health, time, activities, balance, and professionalism, and 3 categories for self-care and the social work program, including academic program experiences, resources, and modeling. Implications of the study in developing and tailoring a self-care program to students in MSW programs are discussed.